Business Model Canvas : Chocolicious / Muhammad Zaki Azid ... [et al.] - Azid, Muhammad Zaki; Kamarul Zaman, Muhammad Amirul Syafiq; Zulkefle, Muhammad Fadhil; Hakim Adli, Nurul Faezatul Husna; Zainal Ayub, Nurjihan Faiqah (2021)
Chocolicious is a local premium chocolate product that not only provides delicious and tasty chocolate, but is also affordable to be enjoyed by everyone. Chocolicious production starts from a small group of chocolate enthusiasts of 5 people, who introduce a product with enjoyable and premium taste. Chocolicious has expanded its distribution network to every state in Malaysia. They are targeting chocolate lovers from all ages including children, teens and adults to grow its consumer by offering both affordable and quality products. To boost their brand image among other chocolate-based brands in Malaysia, Chocolicious has collaborated with a variety of different generations of influencers in social media including from Instagram, Twitter and Tiktok. As social media today is the fastest and easiest way to reach the community. This report will discuss the problem statement of the company established which is Chocolicious, the SWOT analysis of Chocolicious between the other competitors, the opportunity recognition to produce this product and the purpose of the business model canvas. This report will be explained transparently about the elements of the business model canvas of Chocolicious.